Elevated carboxy terminal cross linked telopeptide of type I collagen in alcoholic cirrhosis: relation to liver and kidney function and bone metabolism. Issue 3 (1st March 1999) - Møller, S; Hansen, M; Hillingsø, J; Jensen, J-E B; Henriksen, J H
Abstract : BACKGROUND: The carboxy terminal cross linked telopeptide of type I collagen (ICTP) has been put forward as a marker of bone resorption. Patients with alcoholic liver disease may have osteodystrophy. AIMS: To assess circulating and regional concentrations of ICTP in relation to liver dysfunction, bone metabolism, and fibrosis. METHODS: In 15 patients with alcoholic cirrhosis and 20 controls, hepatic venous, renal venous, and femoral arterial concentrations of ICTP, and bone mass and metabolism were measured. RESULTS: Circulating ICTP was higher in patients with cirrhosis than in controls. No overall significant hepatic disposal or production was found in the patient or control groups but slightly increased production was found in a subset of patients with advanced disease. Significant renal extraction was observed in the controls, whereas only a borderline significant extraction was observed in the patients. Measurements of bone mass and metabolism indicated only a mild degree of osteodystrophy in the patients with cirrhosis. ICTP correlated significantly in the cirrhotic patients with hepatic and renal dysfunction and fibrosis, but not with measurements of bone mass or metabolism. CONCLUSIONS: ICTP is highly elevated in patients with cirrhosis, with no detectable hepatic net production or disposal. No relation between ICTP and markers of bone metabolism was identified, but there was a relation to indicators of liver dysfunction and fibrosis. As the cirrhotic patients conceivably only had mild osteopenia, the elevated ICTP in cirrhosis may therefore primarily reflect liver failure and hepatic fibrosis.